Panel data analysis of the impact of economic and institutional factors upon the FDI inflow in SEE countries - Makrevska disoska, Elena; Toshevska trpchevska, Katerina; Kikerkova, Irena; Naumovska, Elena (My University, 2018)
The panel data analysis presented in this paper focuses on the impact of economic and institutional factors upon the attractiveness of the economies of South- East Europe (SEE): Albania, Bosnia and Herzegovina, Bulgaria, Macedonia, Montenegro, Romania, Serbia, Kosovo and Croatia for foreign direct investment (FDI). The analysis was done for a period of twenty years (1995-2015) in order to examine which determinants are significant for increased FDI inflow in the SEE countries on a basis of a holistic approach using multiple regressions. Taking into account both economic and institutional variables, the results of the analysis indicate both of them to be significant for attracting FDI.
Keywords: foreign direct investment; South-East Europe; CEFTA-2006, panel data analysis, economic factors; institutional factors